Completing the Spectral Mosaic of Chloromethane by Adding the CHD2Cl Missing Piece Through the Interplay of Rotational/Vibrational Spectroscopy and Quantum Chemical Calculations - Mattia Melosso; Paolo Stoppa; Daniela Alvarado-Jiménez; Filippo Tamassia; Carlotta Sapienza; Luca Bizzocchi; Luca Dore; Cristina Puzzarini; Andrea Pietropolli Charmet; Nicola Tasinato (Molecules)
Chloromethane (CH3Cl) is a key chlorinated organic compound not only in atmospheric chemistry, but also in the field of molecular astrophysics and a possible biosignature in exoplanetary atmospheres. While the spectroscopic characterization of the main isotopic species has been addressed in great detail, that of its isotopologues remains incomplete. This work aims at filling this gap by focusing on the bideuterated species, CHD2Cl, and exploiting both rotational and vibrational spectroscopy in combination with state-of-the-art quantum-chemical (QC) calculations. First, the rotational spectrum of CHD2Cl has been measured in the millimeter-wave domain, allowing the accurate determination of several spectroscopic constants for four isotopologues, namely 12CHD235Cl, 12CHD237Cl, 13CHD235Cl, and 13CHD237Cl. The newly determined rotational constants have been used to refine the semi-experimental equilibrium structure of chloromethane. Secondly, the vibrational analysis, supported by high-level QC predictions of vibrational energies, has been conducted in the 500–6200 cm−1 infrared (IR) region, enabling the identification of more than 30 bands including fundamental, overtone, and combination transitions. Finally, chloromethane’s radiative efficiency has been simulated using the QC IR absorption cross-sections, and the effects of isotopologue distribution on the predicted radiative properties have been investigated. All these findings greatly improve the comprehension of the spectroscopic properties of bideuterated chloromethane isotopologues, and of chloromethane in general, and facilitate future terrestrial and extraterrestrial studies.